Compressive behaviour of additively manufactured AlSi10Mg: Druckeigenschaften additiv gefertigter AlSi10Mg Proben. Issue 5 (30th May 2018) - Hitzler, L.; Schoch, N.; Heine, B.; Merkel, M.; Hall, W.; Öchsner, A.
Abstract: The advantages of free form fabrication methods regarding the geometrical flexibility are well known. With the full melting approach of the raw material, as utilized in selective laser melting, this freedom in design is coupled with remarkable mechanical strength. Most studies focused on the tensile characteristics; this study investigates the direction dependent compressive behaviour of selective laser melted AlSi10Mg. The obtained compressive Young's moduli exceeded both the equivalent Young's moduli for the tensile loading and the Young's modulus of the isotropic, conventionally fabricated, bulk base material, ranging as high as 82 GPa. The compressive yield strength was found to be similar to the yield point in tensile loading, with the ultimate compressive stress and strain being far superior to their tensile counterpart.